Factors influencing mortality among alcohol and drug treatment clients in Victoria, Australia: The role of demographic and substance use characteristics - Lloyd, B.; Barratt, Monica; Ferris, J.; Best, D.; Lubman, D. (Sage Publications Ltd., 2013)
Objective: Clinical studies consistently identify alcohol- and drug-related treatment populations as more likely to die prematurely compared with an age-matched general population. However, demographic characteristics and primary drug of concern as predictors of mortality risk following treatment have not been adequately explored. This paper examines relationships between substance use, demographic factors and mortality among alcohol and drug treatment clients. Method: A retrospective cohort incorporating 7 years of data was utilised to examine mortality outcomes in the 2 years following treatment among Victorian clients recorded on the Alcohol and Drug Information Service (ADIS) database by linking partial client identifiers with the National Death Index (NDI). A cohort of 18,686 clients engaged in at least one course of treatment over a 12-month period was included. Analysis was of crude and standardised mortality rates across client groups in terms of the presenting drug of concern for treatment and demographic characteristics. Results: A higher risk of premature death was associated with older age, being male, not being employed, living alone, medical and psychiatric comorbidity, recent injecting, and a history of intensive drug treatment access. Alcohol treatment clients had the worst prognosis. After adjustment for client characteristics, alcohol treatment clients experienced a significantly higher rate of death compared with other clients. Conclusions: Findings from these previously unexplored data highlight the need to increase awareness of the range and magnitude of risks associated with harmful alcohol use, and to identify approaches to enhance treatment effectiveness to reduce negative outcomes following treatment for populations at elevated risk of harm.